In situ coating of a lithiophilic interphase on a biporous Cu scaffold with vertical microchannels for dendrite-free Li metal batteries. Issue 23 (2nd June 2021) - Wang, Li-Min; Ban, Xiao-Kuan; Jin, Zong-Zi; Peng, Ran-Ran; Chen, Chu-Sheng; Chen, Chun-Hua
Abstract : Copper oxide is coated in situ on a phase inversion-derived Cu scaffold for Li metal anodes, which exhibit a low nucleation overpotential, high coulombic efficiency and a long lifespan. The scaffold-Li//NCM full cell exhibits good cycling stability. Abstract : Severe dendrite growth, low coulombic efficiency and huge volume change have impeded the practical application of Li metal anodes, and the construction of porous scaffolds is an effective strategy to stabilize Li metal. Herein, copper oxide (CuO x ) is coated in situ on a unique biporous Cu scaffold (CuO x @Cu) through direct thermal oxidation. CuO x with strong lithiophilicity, confirmed by DFT calculations and experiments, can greatly decrease the nucleation barrier and increase the nucleation sites of Li metal. The reactions of CuO x with Li form Li2 O, which can reinforce the SEI films and regulate ion distribution. Biporous Cu with vertical microchannels and interconnected pores, derived by the phase inversion method, can dissipate local current density and improve the uniformity of Li deposition. As a result, CuO x @Cu demonstrates a nucleation overpotential of 5 mV and a high coulombic efficiency of 98.8% over 520 cycles at 1 mA cm −2, outperforming most of the reported scaffolds. Symmetric cells with CuO x @Cu exhibit much prolonged lifespans and reduced hysteresis in both ether-based and carbonate-based electrolytes. Furthermore, full cells with LiFePO4 cathodes or LiNi0.7 Co0.1 Mn0.2 O2 cathodes exhibit excellent long-term cycling stability and rate capability, demonstrating great compatibility with the current industry and promoting the practical application of Li metal batteries.